CO2 and CH4 in sea ice from a subarctic fjord under influence of riverine input - Crabeck, O.; Delille, Bruno; Thomas, D. R.; Geilfus, Nicolas Xavier; Rysgaard, Søren; Tison, Jean-Louis (2014)
We present the CH4 concentration [CH4], the partial pressure of CO2 (pCO2) and the total gas content in bulk sea ice from subarctic, land-fast sea ice in the Kapisillit fjord, Greenland. Fjord systems are characterized by freshwater runoff and riverine input and based on dδ18O data, we show that > 30% of the surface water originated from periodic river input during ice growth. This resulted in fresher sea-ice layers with higher gas content than is typical from marine sea ice. The bulk ice [CH4] ranged from 1.8 to 12.1 nmol Lg-1, which corresponds to a partial pressure ranging from 3 to 28 ppmv. This is markedly higher than the average atmospheric methane content of 1.9 ppmv. Evidently most of the trapped methane within the ice was contained inside bubbles, and only a minor portion was dissolved in the brines. The bulk ice pCO2 ranged from 60 to 330 ppmv indicating that sea ice at temperatures above -4 °C is undersaturated compared to the atmosphere (390 ppmv). This study adds to the few existing studies of CH4 and CO2 in sea ice, and we conclude that subarctic seawater can be a sink for atmospheric CO2, while being a net source of CH4. SCOPUS: ar.j info:eu-repo/semantics/published